Informed consent in Malaysia: bridging the gap between law and medical practice - Jahn Kassim, Puteri Nemie (2015)
The law relating to informed consent in Malaysia has developed significantly since the abandonment of the Bolam principle by the Federal Court of Malaysia in 2007, which marked the shift away from professional dominance towards recognition of individual autonomy in the area of medical decision-making. The adoption of the “reasonable prudent patient test” by the Federal Court in determining the material risks which the doctor needs to disclose has made circumstances surrounding the patient of utmost importance thereby thrusting the respect for patient autonomy into a more dominated ideology. The subsequent development of judicial cases on informed consent since 2007 has also shown the reinforcement of patient autonomy and the right of self-determination. Although the decision by the Federal Court marked the change in the legal jurisprudential landscape in Malaysia, it has also created gaps in medical practice. Generalised consent forms are no longer adequate without specifically detailing the risks discussed with the patient prior to consent being granted and there is still uncertainty in the practice of informed consent. Factors such as complexity of communication in clinical encounters involving language barriers, advancing medical technology and changing relationship between doctor and patient have undermined informed consent processes. Informed consent should not be understood as being just a theoretical principle but an arduous process covering a spectrum of structural realities and cultural perspectives. Future efforts need to ensure informed consent involve collaborative processes that promotes autonomy, freedom and choice